Analytical solutions for conformable fractional Bratu-type equations - Ilie, Mousa; Biazar, Jafar; Ayati, Zainab (International Journal of Applied Mathematical Research, 2018)
Solving fractional differential equations have a prominent function in different science such as physics and engineering. Therefore, are different definitions of the fractional derivative presented in recent years. The aim of the current paper is to solve the fractional differential equation by a semi-analytical method based on conformable fractional derivative. Fractional Bratu-type equations have been solved by the method and to show its capabilities. The obtained results have been compared with the exact solution.